Esterification of fatty acids with ethanol over layered zinc laurate and zinc stearate – Kinetic modeling. (1st August 2015) - de Paiva, Eduardo Jose Mendes; Sterchele, Stefano; Corazza, Marcos Lúcio; Murzin, Dmitry Yu; Wypych, Fernando; Salmi, Tapio
Abstract : Graphical abstract: Highlights: Modeling of long chain FFA with ethanol was performed using Eley–Rideal approach. No diffusional limitations were found with zinc carboxylic salts. High hydrophobic behavior was observed with zinc laurate. Ethanolysis of FFA reached 92% and catalytic gain compared to blanks reached 40%. Structural changes in the catalyst were observed which exchange FFA with the medium. Abstract: This work is focused on the esterification of fatty acids (commercial oleic mix) with zinc carboxylates (layered metal soap). About 25 experiments were performed, with and without catalyst, yielding a kinetic model based on the Eley–Rideal approach, able to predict fatty acid conversions under different conditions (molar ratio fatty acids/ethanol and temperature). An apparent first order reaction with respect to both reactants with no diffusion limitations was proposed. The activation energy of 80 kJ/mol was found. Fatty acid conversion up to 92% was reached under some conditions and the catalytic yields compared to the blank ones reached 40% in less than 90 min of reaction. This catalyst has shown a unique behavior among all other catalysts available for esterification, acting similarly to a homogeneous catalyst during the reaction but being recovered like a heterogenous catalyst at the end of the process.